An Expatriate from Saudi Arabia with Papulo-nodular Rash and Blisters for Two Years (Journal of Medicine, 2023)
Bangladesh is non endemic for Cutaneous Leishmaniasis (CL). Rarely, we come across such cases in workers returning from Middle east particularly Saudi Arabia. Recently we found and managed a case of cutaneous leishmaniasis in a 37 year old male returning from Saudi Arabia with a lesion behind his left ankle joint. Although Sodium Stibogluconate is the first choice of drug to treat CL, it is not available in Bangladesh. He was managed successfully with Liposomal Amphotericin B. High index of suspicion is needed to diagnose such case without any delay.J MEDICINE 2023; 24(2): 167-168